Class II Division 1 malocclusion treatment using TADs: Case report - Pajević Tina; Juloski Jovana; Živković Marija (Stomatološki glasnik Srbije, 2020)
Introduction Orthodontic treatment of Class II Division 1 (II/1) malocclusions in adults can be challenging since skeletal effects are limited. Possible treatment options are orthodontic camouflage or orthognatic surgery, in severe cases. The aim of this paper was to present a successful management of Class II malocclusion in an adult patient using temporary anchorage devices (TADs). Case report After detailed clinical examination, study models and cephalometric analysis, a 26 years old patient was diagnosed with Class II malocclusion, an overjet of 12 mm, congenitally missing tooth 41 and midline shifted to the right in upper dental arch. In prior orthodontic treatment, patient had upper premolars extracted. Posterior teeth in upper left quadrant were shifted mesially. The camouflage treatment was considered, using temporary anchorage devices (TADs) to distalize posterior teeth on the left side, and gain space for incisor retraction and midline correction in upper dental arch. Results Using TADs as additional anchorage in anterior region and coil spring for molar distalization, the space was made for tooth 23, midline correction and incisor retraction. After 40 months, a satisfactory result was achieved, overjet and midline correction, class I canines occlusion and class II molar occlusion. Conclusion Class II/1 malocclusion in adults can be successfully treated using TADs. The success depends on the severity of malocclusion and patient cooperation.